Development a system of automatic control bore of light guides during forming of the fluid glass - Карпов, Дмитрий Геннадьевич; Яшков, Игорь Олегович (Eastern-European Journal of Enterprise Technologies, 2012)
This article describes the process of developing a system of automatic regulation of the diameter of the fiber glass during forming in computer-aided manufacturing